2004
DOI: 10.1159/000076386
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-Up of a 13-Year-Old Boy with a Pituitary Adenoma Causing Gigantism – Effect of Octreotide Therapy

Abstract: Background/Aim: In children, there is little experience with octreotide therapy for pituitary tumors, especially growth hormone (GH) producing adenomas. We report on a 13-year-old boy with gigantism due to a GH-producing pituitary adenoma caused by a Gsα mutation on the basis of McCune-Albright syndrome. Methods: At the age of 6.5 years a GH- and prolactin-producing pituitary adenoma was diagnosed. The adenoma was surgically removed. Immediately thereafter, the small adenoma residuum was treated with octreotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Medical therapy in acromegalic patients has highly progressed with the availability of dopamine agonists and somatostatin analogues (such as octreotide and lanreotide). In gigantism, treatment with somatostatin analogues has been found to be effective in some cases [8,10,11,12], but not in others, even in combination with cabergoline [13,14,15,16]. Since 2004, pegvisomant, a pegylated GH receptor antagonist, represents a new therapeutic option for the management of patients with acromegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Medical therapy in acromegalic patients has highly progressed with the availability of dopamine agonists and somatostatin analogues (such as octreotide and lanreotide). In gigantism, treatment with somatostatin analogues has been found to be effective in some cases [8,10,11,12], but not in others, even in combination with cabergoline [13,14,15,16]. Since 2004, pegvisomant, a pegylated GH receptor antagonist, represents a new therapeutic option for the management of patients with acromegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of octreotide-LAR to acromegaly in adulthood demonstrated that several patients developed gallstones and impairment of glucose tolerance [16][17][18]. In two previous reports of treatment of GH excess in MAS, no adverse event due to octreotide-LAR was reported [5,12]. Three-year duration of octreotide-LAR is likely to cause side effects in our patient.…”
Section: Discussionmentioning
confidence: 53%
“…Two patients who treated with the combination of cabergoline and octreotide-LAR were children (12 and 14 years-old). Schoof et al [12] reported a 13 year-old boy of MAS and gigantism. They also used octreotide-LAR for one year and it was partially effective for the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young patients with excessive growth hormone secretion their height usually exceeds 3 or 4 SDs. In most of these children the excessive growth hormone secretion results from a pituitary adenoma or hyperplasia, which is genetically determined in a minority of cases [27, 28]. One of these genetic conditions is the McCune-Albright syndrome.…”
Section: Hereditary Causes Of Tall Staturementioning
confidence: 99%